Optimising the quality and outcomes of treatments for diabetic foot infections. Issue 9 (1st September 2016) - Robineau, O.; Nguyen, S.; Senneville, E.
ABSTRACT: Introduction : Infection is the commonest foot complication that arises in people with diabetes and may lead to amputation and even death. The emergence of multidrug resistant bacteria, especially in Gram negative rods, may have a negative impact on the chances of cure in these patients. Areas covered : We searched the Medline and Pubmed databases for studies using the keywords 'diabetic foot infection' and 'diabetic foot osteomyelits' from 1980 to 2016. Expert commentary : Much has been done in the field of diabetic foot infection regarding pathophysiology, diagnosis and treatment. The construction of multidisciplinary teams is probably the most efficient way to improve the patients' outcome. The rational use of antibiotics and surgical skills are essential in these potentially severe infections. Each case of diabetic infection deserves to be discussed in the light of the current guidelines and the local resources. Because of the overal poor outcome of these infections, prevention remains a priority.